Analysis of the safety and efficacy of flow diverter device in the treatment of tandem aneurysms in the internal carotid artery - Wan, Jun; Xu, Ligang; Jiang, Yeqing; Zhang, Lei; Wang, Zhenyu; Zhang, Xiaolong; Wang, Shengzhang (Frontiers in Neurology, 2025)
ObjectiveTo investigate the clinical efficacy and safety of flow diverter device (FDD) in the treatment of tandem aneurysms in the internal carotid artery.Materials and methodsThis study was a retrospectively observational study involving two neurointerventional centers. Sixteen Patients with tandem aneurysms in the internal carotid artery treated with FDD and Digital Subtraction Angiography (DSA) follow-up in Huashan Hospital Affiliated with Fudan University and Jing’an District Central Hospital Affiliated with Fudan University from 2020.08 to 2023.12 were included. The outcomes included the angiographic occlusion rate of aneurysms, complications, and the modified Rankin Scale score. The risk factors of complete occlusion of tandem aneurysms were explored by logistic regression analysis.ResultsA total of 38 aneurysms were included, including 21 aneurysms of 8 patients in the Pipeline Embolization Device (PED) group and 17 aneurysms of 8 patients in the Tubridge Flow Diverter (TFD) group. A total of 16 FDD stents were implanted, 8 in each PED and TFD group, with a technical success rate of 100%. The median value of maximum aneurysm diameter (Dmax) was 4.27 (3.57–5.41) mm. Among them, 28 aneurysms had a maximum diameter of <5 mm (73.7%), 10 aneurysms had a maximum diameter of 5–15 mm (26.3%). All patients were followed up clinically for a median of 25.5 months (15.5–28.7 months). There were no deaths and symptomatic complications. The modified Rankin Scale scores (mRS) of 16 patients were all less than 2. All patients were examined by angiography with a median of 14 months (6–27 months). Among them, there were 5 Consensus Grading Scale for Endovascular Aneurysm Occlusion (CGSFEAO) grade 5 (13.2%), 1 CGSFEAO grade 4 (2.6%), 1 CGSFEAO grade 2 (2.6%) and 31 CGSFEAO grade 0 (81.6%). The complete occlusion rate of intracranial aneurysm in the whole study was 81.6%, including 85.7% in the PED group and 76.5% in the TFD group, and there was no significant statistical difference between the two groups. Statistically significant variables were not found in univariate logistic regression analysis.ConclusionFDD is safe and effective in treating tandem aneurysms in the internal carotid artery with a high occlusion rate and few complications. TFD is comparable to PED in the treatment of intracranial tandem aneurysms.